A matter of life or death: How microsatellites emerge in and vanish from the human genome - Kelkar, Yogeshwar D.; Eckert, Kristin A.; Chiaromonte, Francesca; Makova, Kateryna D.

(untitled) (Genome Research, 2011)
Microsatellites—tandem repeats of short DNA motifs—are abundant in the human genome and have high mutation rates. While microsatellite instability is implicated in numerous genetic diseases, the molecular processes involved in their emergence and disappearance are still not well understood. Microsatellites are hypothesized to follow a life cycle, wherein they are born and expand into adulthood, until their degradation and death. Here we identified microsatellite births/deaths in human, chimpanzee, and orangutan genomes, using macaque and marmoset as outgroups. We inferred mutations causing births/deaths based on parsimony, and investigated local genomic environments affecting them. We also studied birth/death patterns within transposable elements (Alus and L1s), coding regions, and disease-associated loci. We observed that substitutions were the predominant cause for births of short microsatellites, while insertions and deletions were important for births of longer microsatellites. Substitutions were the cause for deaths of microsatellites of virtually all lengths. AT-rich L1 sequences exhibited elevated frequency of births/deaths over their entire length, while GC-rich Alus only in their 3′ poly(A) tails and middle A-stretches, with differences depending on transposable element integration timing. Births/deaths were strongly selected against in coding regions. Births/deaths occurred in genomic regions with high substitution rates, protomicrosatellite content, and L1 density, but low GC content and Alu density. The majority of the 17 disease-associated microsatellites examined are evolutionarily ancient (were acquired by the common ancestor of simians). Our genome-wide investigation of microsatellite life cycle has fundamental applications for predicting the susceptibility of birth/death of microsatellites, including many disease-causing loci.